POPULATION SUPPORT FOR MAKING AN URBAN AREA AND ITS TRANSPORT SYSTEM RESILIENT AGAINST FLOODING - Volce, Cilio José; Soares, Daniela de Castro; Velasco, Manuela Fontenele; Fontenele, Heliana Barbosa; da Silva junior, Carlos Alberto Prado (Revista AIDIS de ingeniería y ciencias ambientales: Investigación, desarrollo y práctica, 2020)
The main objective of this research was to evaluate the population’s support for a project to make resilient an urban area and local transportation system that are subject to flooding. To develop the study, a conceptual project was created that represented a solution to avoid flooding in the aforementioned area. This conceptual project was presented to a group of interviewees for their appraisal. A multiple choice questionnaire was utilized to capture the interviewees’ perceptions about the proposal, as well as their opinions about the possibility of financially supporting the project. For this specific case study, the results indicate that the citizens would financially support the project. Yet, this support would be primarily in the form of volunteer work that would need to be converted into monetary resources. Beyond this, the interviewees were able to express their opinions and concerns about the proposal which was presented in the form of a conceptual project.